2017
DOI: 10.1080/14794802.2017.1318084
|View full text |Cite
|
Sign up to set email alerts
|

A study of creative reasoning opportunities in assessments in undergraduate calculus courses

Abstract: In this article we present the findings of a research study which investigated the opportunities for creative reasoning (CR) made available to first year undergraduate students in assessments. We compared three first year calculus courses across two Irish universities using Lithner's framework. This framework sets apart imitative reasoning (IR) (analogous to rote learning and mimicry of algorithms) and CR (which includes plausible mathematicallyfounded arguments). We report on the differences between reasoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…For example, using this classification, Bergqvist (2007) found, in the Swedish context, that it was possible to pass an introduction to calculus closed book exam by employing only imitative reasoning while the tasks involving creative reasoning consisted mostly in asking students to create specified examples. A similar study in Ireland (Mac an Bhaird et al, 2017) found that there were more creative reasoning tasks in the assessment of mathematics for mathematics students than in the assessment of mathematics for non-mathematics specialists (e.g., engineers) and that for the latter it was possible to achieve high marks in calculus exams by just employing imitative reasoning.…”
Section: Summative Assessment Of Mathematics At University Levelmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, using this classification, Bergqvist (2007) found, in the Swedish context, that it was possible to pass an introduction to calculus closed book exam by employing only imitative reasoning while the tasks involving creative reasoning consisted mostly in asking students to create specified examples. A similar study in Ireland (Mac an Bhaird et al, 2017) found that there were more creative reasoning tasks in the assessment of mathematics for mathematics students than in the assessment of mathematics for non-mathematics specialists (e.g., engineers) and that for the latter it was possible to achieve high marks in calculus exams by just employing imitative reasoning.…”
Section: Summative Assessment Of Mathematics At University Levelmentioning
confidence: 94%
“…Since this situation is likely to be similar in many other countries, as some of the literature reviewed below indicates (see Bergqvist, 2007, for Sweden andMac an Bhaird, Nolan, O'Shea, &Pfeiffer, 2017, for Ireland), it is not surprising that much of the literature on summative assessment of mathematics at university discusses the types of reasoning assessed by closed book exam as they are currently designed. The analysis of types of reasoning elicited by current summative assessment is important for our study in the light of the link posed by Entwistle and Entwistle (1991) between perceived assessment demands and approaches to learning.…”
Section: Summative Assessment Of Mathematics At University Levelmentioning
confidence: 95%
“…Indeed, several studies have shown that students are mainly given tasks that promote the use of predetermined algorithms, procedures, and/or examples of how to solve the task rather than opportunities to engage in a problem-solving struggle without instruction (Stacey and Vincent, 2009;Denisse et al, 2012;Boesen et al, 2014;Jäder et al, 2019). For example, Jäder et al (2019) examined mathematics textbooks from 12 countries and found that 79% of the textbook tasks could be solved by merely following provided procedures, 13% could be solved by minor adjustments of the procedure, and only 9% required students to create (parts of) their own methods (for similar findings, also see Pointon and Sangwin, 2003;Bergqvist, 2007;Mac an Bhaird et al, 2017). In response to these findings, Lithner (2008Lithner ( , 2017 developed a framework arguing that the use of instructions in terms of predefined algorithms has negative long-term consequences for the development of students' conceptual understanding.…”
Section: Introductionmentioning
confidence: 91%
“…Such frameworks enable the study of the types of tasks assigned in university level courses (Kinnear et al, 2020a;Mac an Bhaird et al, 2017), but it seems that very little work has been done in the area of e-assessment.…”
Section: What Developments At the Forefront Of E-assessment (Such As Artificial Intelligence) Can We Apply To University Mathematics?mentioning
confidence: 99%